Curcumin-Loaded mPEG-PLGA Nanoparticles Attenuates the Apoptosis and Corticosteroid Resistance Induced by Cigarette Smoke Extract - Chen, Xi; Wang, Di; Guo, Xuejun; Li, Xiaoming; Ye, Wenjing; Qi, Yang; Gu, Wen (Frontiers in Pharmacology, 2022)
The present study was aim to prepare curcumin-loaded methoxypolyethylene-glycols-poly (lactic-co-glycolic acid) nanoparticles (Cur-mPEG-PLGA-NPs) and investigate curcumin’s effect on reversing corticosteroid resistance induced by cigarette smoke extract (CSE) in rat tracheal epithelial (RTE) cells. The Cur-mPEG-PLGA-NPs were spherical, regular in shape with smooth surfaces, and well distributed and Cur-mPEG-PLGA-NP suspensions had good water solubility and presented prolonged release. Furthermore, we found that Cur-mPEG-PLGA-NPs were internalized more than curcumin into the cells and significantly alleviated apoptosis in RTE cells. In addition, 10% CSE reduced the maximal inhibition percentage and increased the half-inhibitory concentration of budesonide (BUD) on IL-8 secretion, and curcumin restored the efficacy of BUD inhibition. BUD in combination with Cur-mPEG-PLGA-NPs showed higher inhibitory rates for LPS- and CSE-induced IL-8 secretion than that in combination with curcumin. Moverover, the relative expression levels of HDAC2 was reduced after CSE exposure and curcumin could improve HDAC2 expression and reverse CSE-induced corticosteroid resistance. Curcumin in high concentration and Cur-mPEG-PLGA-NPs restored HDAC2 levels in RTE cells and thus Cur-mPEG-PCL-NPs have higher biological activity than curcumin.